Development Of Outdoor Learning-Based Independent Flow Teaching Module to Improve Critical Thinking Abilities in Science Learning in Grade VII of SMP 2 Darul Hikmah, Aceh Jaya District - Aisyah, Aisyah; Jalaluddin, Jalaluddin; Ibrahim, Ibrahim; Andalia, Nurlena; Rafsanjani, Aiza (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The students' critical thinking skills are less than optimal in science learning. This study aims to develop and produce a MERDEKA flow teaching module based on outdoor learning to improve critical thinking skills in science learning in grade VII of SMP 2 Darul Hikmah, Aceh Jaya Regency. This objective is based on the results of the analysis, which shows that students' critical thinking skills are not optimal in science learning. This study uses the Research and Development (R&D) ADDIE model method with three stages, namely Analysis, Design, and Development. The analysis stage is carried out to identify students' needs and problems faced in science learning. The design stage involves planning a learning module that integrates outdoor learning activities with the MERDEKA flow. Module development is carried out by designing interactive and interesting materials and activities. The results of the study concluded that the use of the MERDEKA flow teaching module based on outdoor learning is effective in improving critical thinking skills in science learning in grade VII of SMP 2 Darul Hikmah, Aceh Jaya Regency. This can be seen from the average N Gain score of 0.806498609 with a very effective category